WRH-2412 alleviates the progression of hepatocellular carcinoma through regulation of TGF-β/β-catenin/α-SMA pathway - Mohammed A. F. Elewa; Wagdy M. Eldehna; Ahmed M. E. Hamdan; Samraa H. Abd El-kawi; Asmaa M. El-Kalaawy; Taghreed A. Majrashi; Reham F. Barghash; Hatem A. Abdel-Aziz; Khalid S. Hashem; Mohammed M. H. Al-Gayyar (Taylor & Francis Group, 2023)
Hepatocellular carcinoma is considered one of the most lethal cancers, which is characterised by increasing prevalence associated with high level of invasion and metastasis. The novel synthetic pyrazolo[3,4-b]pyridine compound, WRH-2412, was reported to exhibit in vitro antitumor activity. This study was conducted to evaluate the antitumor activity of WRH-2412 in HCC induced in rats through affecting the TGF-β/β-catenin/α-SMA pathway. Antitumor activity of WRH-2412 was evaluated by calculating the rat's survival rate and by assessment of serum α-fetoprotein. Protein expression of TGF-β, β-catenin, E-cadherin, fascin and gene expression of SMAD4 and α-SMA were determined in hepatic tissue of rats. WRH-2412 produced antitumor activity by significantly increasing the rats' survival rate and decreasing serum α-fetoprotein. WRH-2412 significantly reduced an HCC-induced increase in hepatic TGF-β, β-catenin, SMAD4, fascin and α-SMA expression. In addition, WRH-2412 significantly increased hepatic E-cadherin expression.